The influence of mineralogical composition and alkali reactivity for utilization of some Egyptian crushed granites as a concrete aggregate - Maged El-fakharany; Ahmed Omar; Mahmoud Abdellatif (Journal of Building Materials and Structures)
Egyptian Eastern Desert is rich in many areas that contain granites masses throughout the geological era; some of them show good characteristics of the rock hardness, durability, density and mineralogy. This current research aims to utilize three main types of granite aggregates based on their mineralogical composition and Alkali reactivity with cement during concrete production. The studied granite aggregate can be also classified into red younger granite aggregate, white older granite aggregate and grey older granite aggregate. Evaluating these granite rocks as aggregate used in concrete mixture is interesting by produced three mixes using the three studied granite aggregate symbolized (Red GA), (White GA) and (Grey GA), tested mechanically to give a more detailed for the obtained results to be not restricted for only studied granite aggregate criteria but also to follow the actual reaction of this studied granite aggregate with cement.   It was obtained that all studied granite aggregates within acceptable limits of concrete aggregate by following Egyptian code (ECP-203) although their variation on its mineralogical composition. Some reflections produced from change in mineralogical composition between the three studied granite aggregates exhibited by relative regression in the average physico-mechanical values for both (White and Grey GA) than (Red GA). On the other hand, slight reactive for (Red GA) than others at the age of 28 day. In addition, all produced (Red GA), (White GA) and (Grey GA) mixes were acceptable mechanically with limits of (ECP-203) giving benefit for using all of the studied granite aggregate after their detailed study involving its mineralogical composition and alkali aggregate reactivity (AAR).